Inverted files versus suffix arrays for locating patterns in primary memory - Puglisi, Simon; Smyth, William; Turpin, Andrew (Springer, 2006)
Recent advances in the asymptotic resource costs of pattern matching with compressed suffix arrays are attractive, but a key rival structure, the compressed inverted file, has been dismissed or ignored in papers presenting the new structures. In this paper we examine the resource requirements of compressed suffix array algorithms against compressed inverted file data structures for general pattern matching in genomic and English texts. In both cases, the inverted file indexes q-grams, thus allowing full pattern matching capabilities, rather than simple word based search, making their functionality equivalent to the compressed suffix array structures. When using equivalent memory for the two structures, inverted files are faster at reporting the location of patterns when the number of occurrences of the patterns is high.